Emerging Trends in Curcumin Embedded Electrospun Nanofibers for Impaired Diabetic Wound Healing - Ganesan Padmini Tamilarasi; Manikandan Krishnan; Govindaraj Sabarees; Siddan Gouthaman; Veerachamy Alagarsamy; Viswas Raja Solomon (Applied Nano, 2022)
Chronic wounds impose a significant burden on individuals and healthcare systems all over the world. Through clinical and preclinical investigations, inflammation and oxidative damage have been established as the primary causes of chronic wounds. These skin sores are easily exposed to microorganisms, which in turn cause inflammation and hinder the healing process. Additionally, microorganisms may cause an infection that prevents collagen production and reepithelialization. Curcumin’s antioxidant, anti-inflammatory, and anti-infectious characteristics, among others, have been identified as useful for diabetic wound healing management. However, curcumin has a few disadvantages, such as limited bioavailability, pH-dependent instability, water insolubility, slow cell absorption, and fast intracellular metabolism. These constraints necessitates the development of a suitable transporter to improve curcumin’s stability, bioavailability, therapeutic efficacy, and solubility. In recent years, Electrospun nanofiber mats have been an excellent choice for drug delivery because of their numerous advantages and inherent properties. Electrospun nanofibers have shown considerable promise as wound dressing materials. This review highlights the potential properties and recent advancements in using curcumin-loaded nanofibers for diabetic wound healing.